Dignity, voice, and the terminal sick role within pediatric illness narratives about death and dying - Chua, Ivy Chin Ing (Nanyang Technological University, 2022)
This thesis surveys ten pediatric illness narratives about death and dying to examine three common issues a young patient grapples with: dignity, voice, and the terminal sick role. These pathographies and fictional texts offer fresh perspectives beyond the biomedical model’s narrow focus on curative treatment.